Sinus Balloon Dilation as Treatment for Acute Sphenoid Sinusitis with Impaired Vision for a Child - Yin Zhao; Kangbing Chen; Zonggui Wang (Case Reports in Medicine)
This paper is about sinus balloon dilatation in treatment of acute left sphenoid sinusitis with left impaired vision in a child. Balloon catheter dilatation (BCD) of the sinus ostia is a new technique. It has been shown to be a minimally invasive technique to manage chronic sinusitis. However, this method is rarely used in the treatment of acute sinusitis. So far, we know of no reported cases of sinus balloon dilatation in treatment of this case, especially for children.